MICROBIAL COMMUNITY ANALYSIS WITH PCR-DGGE-SEQUENCING BASED MOLECULAR METHODS IN MUNICIPAL SOLID WASTE MANAGEMENT - Ozkaya, Betamin; Demir, Ahmet (YILDIZ TECHNICAL UNIV, 2011)
In this work, existing studies on Polymerase Chain Reaction (PCR), Denaturing Gradient Gel Electrophoresis (DGGE) and sequence analysis based molecular techniques was included in the solid waste management. In this context, the current studies were examined on landfills and determination of active composting microbial population.
Keywords: Landfill; composting; PCR; DGGE; sequencing; Engineering